2014
DOI: 10.1016/j.jpsychores.2014.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Ecological validity and clinical utility of Patient-Reported Outcomes Measurement Information System (PROMIS®) instruments for detecting premenstrual symptoms of depression, anger, and fatigue

Abstract: Objective This study examined the ecological validity and clinical utility of NIH Patient Reported-Outcomes Measurement Information System (PROMIS®) instruments for anger, depression, and fatigue in women with premenstrual symptoms. Methods One-hundred women completed daily diaries and weekly PROMIS assessments over 4 weeks. Weekly assessments were administered through Computerized Adaptive Testing (CAT). Weekly CATs and corresponding daily scores were compared to evaluate ecological validity. To test clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…Items were answered on a 5-point scale ranging from 1 (never) to 5 (always). Items were summed and converted to standardized T-scores; higher T-scores represent more depressive symptoms 48 . Cronbach's alpha was 0.92-0.94.…”
Section: Methodsmentioning
confidence: 99%
“…Items were answered on a 5-point scale ranging from 1 (never) to 5 (always). Items were summed and converted to standardized T-scores; higher T-scores represent more depressive symptoms 48 . Cronbach's alpha was 0.92-0.94.…”
Section: Methodsmentioning
confidence: 99%
“…End-of-day diaries, in which patients report their symptoms on a daily basis, often represent a viable alternative where EMA is not feasible or not desirable (e.g., when respondents are not able to respond to momentary prompting) [3638]. End-of-day ratings require some degree of retrospection (typically, a 24-hr recall period is used).…”
Section: Diary Methods In Pro Measurement: Rationale and Optionsmentioning
confidence: 99%
“…Studies comparing recall ratings with aggregated diary ratings over the same reporting period have usually found that symptoms tend to be recalled at higher levels relative to momentary and end-of-day ratings, a phenomenon sometimes referred to as the “experience memory gap” [47]. This effect appears to be robust especially for physical symptoms and negative affective experiences, which are generally rated as more intense, more frequent, and longer lasting in recall [38,40,4851]. The magnitude of this “gap” between retrospective and diary ratings has been found to be similar for relatively shorter (7-day) and longer (30-day) reporting periods [45,36].…”
Section: Use Of Diaries For Evaluating Ecological Validity and Recallmentioning
confidence: 99%
See 1 more Smart Citation
“…High scores suggest a high level of distress while low scores suggest a low level of distress. Fatigue over the past week was assessed using the self-administered 7-item Patient Reported Outcomes Measurement Information System (PROMIS) fatigue scale short form [25] , [26] questionnaire which has been validated in women with premenstrual symptoms [27] and in osteoarthritis patients [28] .…”
Section: Methodsologymentioning
confidence: 99%